2013
DOI: 10.4161/onci.23849
|View full text |Cite
|
Sign up to set email alerts
|

TIM3+FOXP3+regulatory T cells are tissue-specific promoters of T-cell dysfunction in cancer

Abstract: T-cell immunoglobulin mucin 3 (TIM3) is an inhibitory molecule that has emerged as a key regulator of dysfunctional or exhausted CD8+ T cells arising in chronic diseases such as cancer. In addition to exhausted CD8+ T cells, highly suppressive regulatory T cells (Tregs) represent a significant barrier against the induction of antitumor immunity. We have found that the majority of intratumoral FOXP3+ Tregs express TIM3. TIM3+ Tregs co-express PD-1, are highly suppressive and comprise a specialized subset of tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
225
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 273 publications
(235 citation statements)
references
References 31 publications
7
225
2
1
Order By: Relevance
“…The unique presence of Tim-3 þ Tregs in tumor tissue has also been observed in multiple preclinical models, including both transplantable and de novo tumors (21). In these models, the Tim-3 þ Treg population has been shown to predominate in tumor tissue and to be more immunosuppressive than the Tim-3 À Treg population, likely as a result of increased production of IL-10 and other key effector molecules such as perforin and granzymes.…”
Section: Tim-3 In T Cells In Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…The unique presence of Tim-3 þ Tregs in tumor tissue has also been observed in multiple preclinical models, including both transplantable and de novo tumors (21). In these models, the Tim-3 þ Treg population has been shown to predominate in tumor tissue and to be more immunosuppressive than the Tim-3 À Treg population, likely as a result of increased production of IL-10 and other key effector molecules such as perforin and granzymes.…”
Section: Tim-3 In T Cells In Cancermentioning
confidence: 94%
“…In these models, the Tim-3 þ Treg population has been shown to predominate in tumor tissue and to be more immunosuppressive than the Tim-3 À Treg population, likely as a result of increased production of IL-10 and other key effector molecules such as perforin and granzymes. Moreover, it has been suggested that Tim-3 þ Tregs have a specific role in actively promoting the development of a dysfunctional phenotype in CD8 þ TILs (21).…”
Section: Tim-3 In T Cells In Cancermentioning
confidence: 99%
“…We found that both the frequency of granzyme B + cells as well as the expression level of granzyme B was increased in CD8 + TILs from Tigit -/-mice after stimulation ( Figure 4C). We further examined the effect of TIGIT deficiency on antigen-specific cytokine responses in either B16F10 melanoma or MC38 colon carcinoma Among the genes upregulated in TIGIT + Tregs in TILs, Havcr2 was of particular interest, as we had previously found that TIM-3 is uniquely enriched on Tregs that accumulate in tumor tissue and express high levels of both IL-10 and perforin (25). Examination of TIM-3 and TIGIT expression in Tregs from naive and tumor-bearing mice showed that while TIM-3 was expressed on a fraction of TIGIT + Tregs in naive mice, all of the TIGIT + Tregs in tumor tissue expressed TIM-3, and at a much higher level than that observed in naive Tregs ( Figure 3D).…”
Section: 5mentioning
confidence: 99%
“…These findings suggest that selective intratumoral inactivation and conversion of CD4 Tregs through targeting Helios may represent an effective approach to cancer immunotherapy. and TIGIT, that are associated with robust immunosuppressive activity as well as dysfunctional tumor-infiltrating lymphocytes (TILs) (3,9). However, the impact of the Treg-specific Helios TF has not been investigated.…”
Section: Treg Stabilitymentioning
confidence: 99%